Nonlinear Dynamic Characteristics of the Curve-face Gear Transmission System - Liu Jun; Zhang Yanxia; Pan Jiezong; Wang Xuesong (Jixie chuandong)
In order to study the nonlinear dynamic characteristics of the curve-face gear transmission system and the influence of parameters on the dynamic characteristics of the system, a nonlinear dynamic model of the curve-face gear system is established. The dimensionless meshing frequency is selected as the control parameter, and the bifurcation diagram, phase diagram, time history diagram and Poincaré diagram are analyzed. The mapping graph is used to study the dynamic characteristics of the system. The results show that the system changes from the non-impact state to the unilateral impact state by jumping bifurcation, and then leads to chaotic motion by continuous doubling bifurcation. When the comprehensive transmission error is increased or the torque is reduced, the non-impact state region of the system shrinks gradually, and the jumping bifurcation value and doubling bifurcation advance, which make the system jump ahead of time. The mode of transition from non-shock to unilateral shock changes, the subharmonic motion region expands gradually and moves forward, the types of motion increase, the number of motion cycles increases, the chaotic motion region expands gradually, and the stability of the system decreases.